Diffuse Idiopathic Skeletal Hyperosteosis: A Review - Sevgi İkbali Afşar (Galenos Yayinevi, 2015)
Diffuse idiopathic skeletal hyperosteosis (DISH) is also known as Forestier disease and is a systemic non-inflammatory disorder seen more commonly in males and elderly. It is characterized by calcification of the anterior longitudinal ligament of the vertebral column and various extraspinal ligaments. It is usually asymptomatic while the most common symptoms are spinal pain, limited range of spinal motion and dysphagia due to esophagus compression. The etiopathogenesis is not clear. It is commonly seen together with diabetes mellitus, obesity, hyperinsulinemia, hypertension and lipid and purine metabolism disorders, indicating an association with metabolic disorders. Recent studies have emphasized that the pathological calcification of the anterior longitudinal ligament plays a role in the pathophysiology. The aim of this study was to summarize new pathogenetic, clinical and therapeutic insights of this disease, based on published literature.